Ultrasound-assisted extraction of polyphenols from Phyllanthi Fructus: Comprehensive insights from extraction optimization and antioxidant activity - Haixia Che; Rui Zhang; Xianyao Wang; Hong Yu; Xuepeng Shi; Jie Yi; Jiawen Li; Qi Qi; Ruizhi Dong; Qian Li (Ultrasonics Sonochemistry)
Phyllanthi Fructus (PF) is a valuable botanical resource with a long history of traditional use, known for potent antioxidant and anti-inflammatory effects attributed to its rich contents of bioactive compounds, particularly polyphenols. However, current extraction techniques limit the utilization of polyphenols from PF. This study aimed to achieve the maximum polyphenol yield and improve the antioxidant activity of PF extracts to promise PF’s prospects for modern healthcare.Firstly, ultrasonic-assisted extraction (UAE) was employed to extract the polyphenols in PF and a combination of Plackett-Burman designs (PBD) and response surface methodology (RSM) was applied to optimize UAE’s conditions. Next, cellular superoxide dismutase (SOD) and malondialdehyde (MDA) were used to assess the antioxidant activity of extracted polyphenols. Ultra-Performance Liquid Chromatography coupled with Quadrupole Time-of-Flight Mass Spectrometry (UPLC-Q-TOF MS) was utilized to characterize polyphenol components in the PF extracts. Finally, network pharmacology and molecular docking analysis were performed to screen the potential target proteins of polyphenols from PF.As a result, the optimized polyphenol yield was 213.49 mg/g, and the antioxidant activities, measured by ability of DPPH scavenging, ABTS+ scavenging, and FRAP were 76.95 %, 2.24 mmol/g, 2.34 mmol/g, respectively. PF extracts also showed good antioxidant capabilities at cellular level. 26 polyphenol components were identified in the PF extracts. Among these, ellagic acid, myricetin, and eriodictyol may exert antioxidant effects by interacting with AKT serine/threonine kinase 1 (AKT1).In conclusion, our study provides valuable insights into the optimizing PF extraction and underscores its potential applications in enhancing natural polyphenols extraction using UAE with a combination of PBD and RSM. These findings offer a promising avenue for the development and utilization of PF, and could serve as a reference for similar extraction processes in the future.